Increased Intracranial Volume: A Clue to the Etiology of Idiopathic Normal-Pressure Hydrocephalus? - Bradley, William G.; Safar, Francis G.; Hurtado, Claudia; Ord, Justin; Alksne, John F. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: The etiology of idiopathic normal-pressure hydrocephalus (NPH) is unknown. The purpose of this study was to examine the hypothesis that NPH begins in infancy as benign external hydrocephalus due to decreased uptake of CSF by the arachnoid villi. Since this occurs before the sutures fuse, a secondary hypothesis is that the intracranial volumes of patients with NPH should be larger than those of healthy individuals.METHODS: Intracranial volumes of 51 patients with clinically suspected NPH were compared with those of age- and sex-matched control subjects. All patients underwent phase-contrast CSF velocity MR imaging. They had aqueductal CSF stroke volumes of at least 60 μL, which was 50% higher than previously published normal values. Intracranial volumes were measured and compared between groups.RESULTS: The average intracranial volume for men with NPH (n = 22) was 1682 mL compared with 1565 for male control subjects (n = 55). The NPH volume averaged 118 mL (7.5%) larger than the control volume (P = .003). The average intracranial volume for women with NPH (n = 29) was 1493 mL compared with 1405 mL for female control subjects (n = 55). The NPH volume was 88 mL (6.3%) larger than the control volume (P = .002).CONCLUSION: Patients with NPH have intracranial volumes significantly larger than normal, suggesting that the initial insult occurs before the sutures fuse at 1 year of age. The patients somehow remain asymptomatic until their later years, when a second insult must occur, leading to symptomatic NPH.